Investigation and cause analysis of the psychological status of nursing staff under the normalization of epidemic prevention and control (常态化疫情防控期间护理人员心理状况调查及原因分析) - ZHAO Jialu (赵佳璐); XIANG Wensheng (相文胜); WANG Huaxin (王华新); DONG Yuxia (董玉霞) (中西医结合护理)
Objective To investigate the psychological state of nursing personnel under the normalization of epidemic prevention and control, and analyze relevant factors in order to provide a basis for nursing managers to carry out human resource management. Methods A survey of 256 nurses in a tertiary hospital was conducted using a general questionnaire, an anxiety self-assessment scale (SAS), and a general happiness scale (GWB). Results The total average score of anxiety in 256 nurses was (48. 37±11. 30) and the overall average score of overall happiness was (73. 99±14. 34). Year of service was a major factor affecting the state of psychological anxiety of caregivers. Overall happiness was associated with anxiety, and a decrease in anxiety increases happiness. Conclusion The survey results showed that there were different degrees of anxiety among nursing personnel under the normalization of epidemic prevention and control, and nursing managers should pay attention to the mental health of nursing personnel, strengthen the psychological knowledge learning of nursing personnel and timely psychological counseling, improve the overall happiness of nursing personnel, and then improve the overall psychological level of nursing staff. (目的 调查常态化疫情防控期间护理人员心理状态, 分析相关因素, 以期为护理管理者开展人力资源管理提供依据。方法 采用一般资料问卷、焦虑自评量表(SAS)和总体幸福感量(GWB)表对某三甲医院256名护士进行调查。结果256名护士焦虑总均分为(43. 37±11. 30)分, 总体幸福感总均分为(73. 99±14. 34)分。工作年限是影响护理人员心理焦虑状态的主要因素。总体幸福感与焦虑有关, 焦虑感降低则幸福感增强。结论 常态化疫情防控期间护理人员存在不同程度的焦虑, 护理管理者应关注护理人员心理健康, 加强护理人员的心理知识学习以及及时进行心理疏导, 提高护理人员总体幸福感, 进而提高护士人员整体心理水平。)